Ethical Spillovers in Firms: Evidence from Vehicle Emissions Testing - Pierce, Lamar; Snyder, Jason (Management Science, 2008)
In this paper, we explore how organizations influence the unethical behavior of their employees. Using a unique data set of over three million vehicle emissions tests, we find strong evidence of ethical spillovers from firms to individuals. When inspectors work across different organizations, they adjust the rate at which they pass vehicles to the norms of those with whom they work. These spillovers are strongest at large facilities and corporate chains, and weakest for the large-volume inspectors. These results are consistent with the economics literature on productivity spillovers from organizations and peers and suggest that managers can influence the ethics of employee behavior through both formal norms and incentives. The results also suggest that employees have persistent ethics that limit the magnitude of this influence. These results imply that if ethical conformity is important to the financial and legal health of the organization, managers must be vigilant in their hiring, training, and monitoring to ensure that employee behavior is consistent with firm objectives.